Effects of chlorogenic acid against aluminium neurotoxicity in ICR mice through chelation and antioxidant actions. (January 2018) - Wang, Xiaomei; Xi, Yu; Zeng, Xiangquan; Zhao, Handong; Cao, Jiankang; Jiang, Weibo
Highlights: CGA attenuates Al-induced memory impairment of mice. CGA chelation promoted Al excretion and reduced its accumulation in hippocampus. CGA protected against Al-induced oxidative stress in hippocampal neurons. CGA promoted the activities of enzymes and attenuated the rate of ATP hydrolysis. CGA antioxidation protected neurons via Nrf2-ARE signalling pathway. Abstract: Aluminium (Al), a potent neurotoxin, can induce oxidative stress and cause cognitive damage, which are associated with Alzheimer's disease. To investigate whether chlorogenic acid (CGA) may influence Al-induced neurotoxicity, aluminium chloride (35 mg Al/kg/day, i.g.) was chronically administered in mice pre-supplemented with CGA (50, 100 and 200 mg CGA/kg/day, i.g.) for 42 days. The results show that CGA attenuated Al-induced memory impairment, Al 3+ accumulation, oxidative stress, mitochondrial damage, and nuclear pyknosis in the hippocampus. Administration of CGA remarkably promoted the antioxidant activities of superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase and attenuated the rate of ATP hydrolysis. The antioxidant action of CGA could protect neurons against Al-induced oxidative stress by increasing the expression of nuclear factor-E2-related factor and its target phase II enzymes. Our findings show that CGA exhibits neuroprotective effects against Al-induced cognitive dysfunction through chelation and antioxidant actions.